The prevalence, severity, and mechanism of breast injuries in elite women`s cricket - McGhee, D.; Potter, E.; Anthony, R. (Journal of Science and Medicine in Sport, 2024)
Introduction: Breast injuries in women's cricket have not been investigated despite their similarity to softball in equipment and play, where breast injury prevalence is 60%. A greater understanding of breast injuries in women's cricket is required to ensure player welfare of the females involved worldwide, being the second-highest participated female sport, with increasing professional opportunities for women. Aim: To investigate the prevalence, severity, and mechanism of breast injury in international women's cricket. Methods: An anonymous, online survey collected cross-sectional, retrospective data on breast injuries' prevalence, severity, mechanism, and prevention strategies in 89 international female cricket players, from 31 countries, competing at the Fairbreak Invitational 2022 International Cricket Competition. Mean age 29.5 ± 5.3 years; mode size 12B bra size (range 8A-14G), International Cricket Council (ICC) rankings: Full Member countries n=37 (42%), Associate Member countries n=52 (58%). Frequency analysis and percentages were tabulated and calculated. Mann-Whitney U-tests and Chi-Squared Tests compared participant characteristics of athletes (age, breast size rank, years played, ICC ranking) who did and did not report breast injuries (p < 0.05). Results: 29% (n=26) reported a previous breast injury. However, over the mean cricket career duration of 13.5 years (95% CI; 12.5-14.5 years), 27 % reported one injury, 65% 2-5, and 11% had 5-10 injuries. 89% (n=23) of injuries were not reported to coaching or medical staff, and 81% (n=70) reported not knowing to report their injury. Breast injury severity ranged from mild to severe. Bruising, swelling, and pain lasted for 1-3 days for 54% and 1-2 weeks for 15%. Long-term changes to breast tissue were reported by 12% (n=3). Most athletes (96%, n=25) continued to play with their injury; 15% (n=4) perceived it negatively affected their ability to run, throw and focus on the game. The most common mechanism of injury was impact with a cricket ball (85%, n=22). Breast protective equipment (BPE) was used by 3% (n=3). No significant difference was found in injury prevalence with participant characteristics (P>0.05). Discussion: The frequency of breast injuries over the respondent`s entire career suggests that the risk of breast injury in international women`s cricket is low. However, based on the duration of bruising, swelling, and pain, over half the injuries warranted treatment that was not received because of non-reporting, and a minority of breast injuries were ranked as severe and had long-term consequences. The high percentage of injuries not reported was attributed to insufficient understanding that breast injuries could be treated. Batting skills training is a potential prevention strategy, being the most common mechanism of injury. The low frequency of injury and low percentage of BPE users suggest it has a limited role in injury prevention. The homogeneity of the skill level, experience, and breast size cautions the interpretation of the lack of difference in prevalence with participant characteristics. Impact/Application to the field: Evidence of the low prevalence of breast injuries in women`s cricket and the need for athlete education to address the lack of reporting of breast injuries because the severity of many injuries warrants treatment, and a minority has long-term consequences. Declaration: My co-authors and I acknowledge that we have no conflict of interest of relevance to the submission of this abstract.